Tensile Strength and Impact Toughness of an AA 7075-T6 Alloy Effects of Aging Temperature and Time During Retrogression Treatment - Karaaslan, Ahmet; Kaya, Isik; Atapek, Hakan (WALTER DE GRUYTER GMBH, 2008)
In this study retrogression and aging treatment have been applied to the samples of an aluminum alloy AA 7075-T6. The retrogression treatment has been performed with different temperatures and times and then aging treatment has been applied at 130 degrees C for 12 h. By determining the effects of the retrogression treatment temperatures and times on the samples, the microstructral and also mechanical changes in AA 7075-T6 alloy have been examined. All microstructures have been investigated by Scanning Electron Microscopy (SEM). Additionally, the mechanical properties have been determined by the notched impact test and the tensile test.
Keywords: ZN-MG ALLOYS; PRECIPITATION; Materials Science